The persistence of memory: The fate of ancient sedimentary organic carbon in a modern sedimentary system - Blair, N. E.; Leithold, E. L.; Ford, S. T.; Peeler, K. A.; Holmes, J. C.; Perkey, D. W. (Geochimica Et Cosmochimica Acta, 2003)
The cycle of organic carbon burial and exhumation moderates atmospheric chemistry and global climate over geologic timescales. The burial of organic carbon occurs predominantly at sea in association with clay-sized particles derived from the erosion of uplifted continental rocks. It follows that the history of the fine-grained particles on land may bear on the nature of the organic carbon buried. In this study, the evolution of clay-associated organic matter was followed from bedrock source to the seabed in the Eel River sedimentary system of northern California using natural abundance C-13 and C-14 tracers. Approximately half of the fine-grained organic carbon delivered to the shelf is derived from ancient sedimentary organic carbon found in the uplifted Mesozoic-Tertiary Franciscan Complex of the watershed. The short residence time of friable soils on steep hill slopes, coupled with rapid sediment accumulation rates on the shelf-slope, act to preserve the ancient organic carbon. A comparable quantity of modem organic carbon is added to particles in the watershed and on the shelf and slope. The bimodal mixture of ancient and modem C in soils and sediments may be characteristic of many short, mountainous rivers. If the Eel River chemistry is typical of such rivers, more than 40 Tg of ancient organic C may be delivered to the world's oceans each year. A flux of that magnitude would have a significant influence on marine and global C-cycles. Copyright (C) 2003 Elsevier Science Ltd.
634jvTimes Cited:143Cited References Count:63